EXPRESSION OF CONCERN: Individual Intervention and Assessment of Students’ Physical Fitness Based on the "Three Precision" Applet and Mixed Strategy Optimised CNN Networks - Zhang, Daomeng (EAI Endorsed Transactions on Pervasive Health and Technology, 2024)
Concerns have been raised over the peer review and editorial processes involving this article. The full notice can be found here: https://doi.org/10.4108/eetpht.11.12717